Psychological Analysis of Informational Materials: Establishing a New Type of Forensic Psychological Evaluation and a New Forensic Science Specialty - Т. N. Sekerazh (Теория и практика судебной экспертизы)
The need for the imposition of the new expert specialty stems from the law enforcement agencies’ demand for psychological research of informational materials in cases involving extremism and terrorism display, indecent assaults on the Internet, corruption oﬀences, inducement and instigation of suicide, propaganda of nontraditional sexual relations among minors, propaganda of Nazi symbols and emblems and many others. Formation particularities of the new type of forensic psychological expertise and the new expert specialty ‘Psychological research of informational materials’ in the Russian Ministry of Justice forensic institutions are contemplated. The defnitions of subject and objects of this type of expertise as well as of the term ‘informational material’ are given. In the context of experts’ further vocational retraining problem it is underscored that during the public forensic experts’ preparation for the Russian Federal Centre of Forensic Science of the Russian Federation Ministry of Justice system an innovative author’s further vocational training programme in expert specialty ‘Psychological research of informational materials’ is used. Meanwhile some non-State organizations, the so-called non-proft organizations, providing educational and certifcation services in the forensic feld apply the same specialty description furnishing non-original content. As a result, the members of law enforcement agencies and judges appointing an expertise form a misconception about the qualifcation of the experts having such certifcates. The unifcation of experts’ training programmes for state and non-state organizations can change the situation and improve the quality of services in forensic psychology as well as the implementation of mandatory experts’ certifcation, training programmes and materials licensing and the governmental control of the certifying organizations.